The practicality of popular scientific books diversity of crab species in the Tabanio mangrove area - Miftahul Jannah; Aminuddin Prahatama Putra; Dharmono Dharmono (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
The problem that occurs in the invertebrate zoology course is that there are no innovative teaching materials related to the diversity of crab species. One of them is in the Tabanio mangrove area to explore students' critical thinking skills. This makes it necessary to develop learning resources in popular scientific books containing material with examples from the surrounding or local environment. This study aims to describe the practical of contents, expectations and actual prototypes of popular scientific books on the diversity of crab species. This research uses stages of development through formative evaluation based on Tessmer, which consists of self-evaluation, expert test, individual test, small group test, and field test and also the content practicality assessment instrument too. The results showed that a popular scientific book was declared very valid based on expert validation results with an average of 88,46%, while based on a one-to-one with an average of 92,31%. This popular scientific book is declared practical because student responses 89,29% with criteria of strongly agreeing and the implementation of popular scientific books 90,00% with outstanding criteria. Therefore, this popular scientific book can be used as an enrichment student on the ability to think critically.Abstrak Masalah yang terjadi pada mata kuliah zoologi invertebrata adalah belum adanya bahan ajar yang inovatif terkait materi keanekaragaman spesies kepiting salah satunya di kawasan mangrove Tabanio untuk menggali kemampuan berpikir kritis mahasiswa. Hal inilah yang membuat perlunya pengembangan sumber belajar berbentuk buku ilmiah popular yang memuat materi dengan contoh-contoh dari lingkungan sekitar atau lokal. Penelitian ini bertujuan untuk mendeskripsikan kepraktisan isi, harapan dan aktual prototipe buku ilmiah popular yang berjudul “Keanekaragaman Spesies Kepiting di Kawasan Mangrove Tabanio”. Metode penelitian ini menggunakan tahap-tahap pengembangan melalui evaluasi formatif berdasarkan Tessmer yang terdiri dari evaluasi diri, uji pakar, uji perorangan, uji kelompok kecil dan uji lapangan serta instrumen penilaian kepraktisan  isi juga mengacu pada Tessmer. Berdasarkan hasil validasi ahli, buku ilmiah popular termasuk kedalam kriteria sangat valid dengan rata-rata 88,46%, sedangkan uji perorangan diperoleh nilai sebesar 92,31%. Buku ilmiah popular ini dinyatakan praktis, karena respons mahasiswa 89,29% dengan kriteria sangat baik dan keterlaksanaan sebesar 90,00% dengan kriteria sangat baik. Oleh karena itu, buku ilmiah popular ini dapat digunakan sebagai bahan pengayaan terhadap kemampuan berpikir kritis mahasiswa.